Laser doppler flowmetry in assessing the effectiveness of treatment of chronic demodex blefaritis - T. N. Safonova; N. P. Kintyukhina; V. V. Sidorov; O. V. Gladkova (Российский офтальмологический журнал, 2018)
Purpose: to study the possibilities of laser Doppler flowmetryin assessing the effectiveness of treatment of chronic Demodex blepharitis. Material and methods. The study included 33 patients (66 eyes), divided into the main and the control groups, identical in gender and age structure. The main group consisted of 16 patients (32 eyes) with chronic Demodex blepharitis. The control group included 17 patients (34 eyes) with no signs of changes in the structures of the anterior eye segment. In addition to the standard ophthalmologic examination, the patients underwent an eyelid skin microcirculation examination (using the Analyzer of peripheral blood and lymph flow LASMA MC-1 and laser diagnostic complex LASMA MC, produced by LASMA firm). The patients of the main group used Dexodem Phyto cream gel for 45 days, whereupon, after 1.5 months, an efficacy control examination was performed. Results. In the main group, typical microcirculatory disorders - arterial hyperemia of the upper eyelid and lower eyelid ischemia, and insufficient activity of the lymph of the upper eyelid - were revealed prior to treatment. After treatment, positive changes were clinically observed. Microcirculation parameters, including the perfusion and the amplitude-frequency spectrum of blood flow of both eyelids approached the normal values, and the activity of the lymphatic system improved. Conclusion. The laser Doppler flowmetry enables the examination of blood flow and lymph flow in inflammatory diseases of the eyelids, in particular blepharitis, and may be considered as an objective method of treatment effectiveness evaluation // Russian ophthalmological journal. 2017; 10 (2): 62-6. (in Russian). doi: 10.21516/2072-0076-2017-10-2-62-66.